Towards a new conceptualization of depression in older adult cancer patients: a review of the literature. (1st December 2016) - Saracino, Rebecca M.; Rosenfeld, Barry; Nelson, Christian J.
Abstract : Objectives: Identifying depression in older adults with cancer presents a set of unique challenges, as it combines the confounding influences of cancer and its treatment with the developmental changes associated with aging. This paper reviews the phenomenology of depression in older adults, and individuals diagnosed with cancer. Method: PsychInfo, PubMed, Web of Science, and Google Scholar databases were searched for English-language studies addressing the phenomenology, symptoms, or assessment of depression in older adults and those with cancer. Results: The Diagnostic and Statistical Manual for Mental Disorders (DSM) criteria that appear to be relevant to both older adults and cancer patients are anhedonia, concentration difficulties, sleep disturbances, psychomotor retardation/agitation, and loss of energy. Possible alternative criteria that may be important considerations included constructs such as loss of purpose, loneliness, and irritability in older adults. Among cancer patients, tearfulness, social withdrawal, and not participating in treatment despite ability to do so were identified as potentially important symptoms. Conclusions: Current DSM criteria may not adequately assess depression in older cancer patients and alternative criteria may be important to inform the understanding and identification of depression in this population. Enhancing diagnostic accuracy of depression is important as both the over-diagnosis and under-diagnosis is accompanied with significant costs. Thus, continued research exploring the phenomenology and identifying effective indicators of depression in older cancer patients is needed.